Analisis Perbandingan Progressive Muscle Relaxation dan Slow Deep Breathing Exercise terhadap Penurunan Hipertensi pada Masyarakat Pesisir di Kecamatan Taniwel - Windarti Rumaolat; Idham Soamole; Wiwi Rumaolat (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
The challenge of health development in Indonesia is the shift in disease patterns, where the burden of disease is no longer dominated by infectious diseases but also by non-communicable diseases such as hypertension, especially in coastal areas where access to healthcare services is difficult. Therefore, non-pharmacological treatments are needed to address healthcare accessibility for coastal communities, namely PMR and SDBE therapies. This study aims to compare PMR and SDBE therapies in reducing hypertension among coastal communities. The method used is a quasi-experimental design, specifically a randomized pretest and posttest three-group design without a control group. The sample size consisted of 90 respondents, with 30 respondents in each intervention group, selected using purposive sampling techniques. The instruments used included questionnaires and standard operating procedures (SOPs). Data analysis was conducted using the Wilcoxon Signed Rank Test and ANOVA. Statistical tests showed that PMR had a very significant effect on reducing blood pressure, SDBE also had an effect on reducing blood pressure, and both PMR and SDBE influenced blood pressure reduction in coastal communities. The ANOVA test results indicated a significant difference in the mean reduction of blood pressure among the groups studied, with a p-value of 0.002. PMR, SDBE, and the combination of both interventions were all effective in lowering blood pressure, showing differences among the three interventions.